AUDIT INTERNAL DALAM PERUSAHAAN KELUARGA : PENDEKATAN INTERAKSI SIMBOLI - Esi Susirawati, Rizka Indri Arfianti (Jurnal Akuntansi, 2015)
This study is a qualitative research using Symbolic Interaction aprroach. The collection of data research with in-depth interviews and field observations. Informants research is Manager of Internal Audit and Internal Audit Supervisor. The author not only do formal interviews, but also with non-formal interview. Manuscripts obtained from the interviews was analyzed and discussed with the model selection three steps Miles and Huberman (1984) as well as the intepreting analysis of Herbert Blumer (1969). Research results show owner / shareholder of a family company is doing dishonesty by means of using a financial company for personal gain. As auditors, the internal audit manager can not do anything because the owner / shareholders still hold full operational control over the company.Conclusions from this research is that even though the level of manager has been filled entirely by professional and performance management at this family company has been quite effective and efficient, but in this family company the function of auditor become less independent and can not work optimally because owner / shareholders who still full control over the company.Keywords: Symbolic Interaction, Internal Auditor, the Company Family